Analysis of Multilayered Ground Amplification Characteristics by Scaled-Down Model Tests - Jin, Yong; Kim, Daehyeon; Jeong, Sugeun; Kim, Hoyeon (Applied sciences, 2022)
During an earthquake, seismic waves travel through different media through the source to reach the surface. It is very necessary to study the dynamic characteristics of soil between different layers during earthquake. In order to explore the dynamic characteristics of soil under the action of ground seismic input motion, scaled-down model tests were carried out through 1 g shaking table tests based on a laminar shear box. After creating a dense lower ground with a sample of mixed silica and silty soil, and a loose upper ground with sand, the acceleration was measured by applying seismic loading through the 1 g shaking table test. Through the Peak ground acceleration, Spectral acceleration and Spectral acceleration amplification factors, the magnification variation and differences of each depth of the model and the dynamic characteristics of soil between different layers were displayed. In order to verify the reliability of the experimental data, a one-dimensional ground response analysis was carried out using DEEPSOIL software. The approximate results obtained by comparing each other can provide a basis for the accuracy of the experimental results.